The Representation of Masculinity in Men's Health Magazine on Advertisements - Mohamad Ramdhan; Lisetyo Ariyanti; Laily Maulida Septiana Harti (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
Advertisements become engaging media to introduce and promote products. Men as masculine creation become one of interesting visual to represent the product and engage the target market. This study aims to discuss the visual and linguistic elements in the advertisements. In addition, this study reveals the interplay of those elements to make meaning and masculinity portrayal in the advertisements. The data are Nivea Crème, Pond’s face wash, Versace Eros perfume, and Skechers shoes. The theory used in this study is visual images by Kress and van Leeuwen (2006) and SF-MDA by Halliday and Matthiessen (2004), supported Generic Structured Potential by Cheong’s framework (2004). This research used the descriptive qualitative method. Therefore, it is in the form of words, sentences, and images. The result of this study indicates that the representation of masculinity is changing over time. Masculinity portrayal such as stylish, independence, actives in sport, and character such as adventurous, strong, calm, muscular body are found in the data. The producer uses process material with goal, attributive, circumstance to represent the product to the targeted market.